Injectisome T3SS subunits as potential chaperones in the extracellular export of Pectobacterium carotovorum subsp. carotovorum bacteriocins Carocin S1 and Carocin S3 secreted via flagellar T3SS - Wu, Huang-Pin; Derilo, Reymund C.; Chen, Han-Ling; Li, Tzu-Rung; Lagitnay, Ruchi Briam James S.; Chan, Yung-Chieh; Chuang, Yutin; Chuang, Duen-Yau (BMC microbiology, 2021)
Pectobacterium carotovorum subsp. carotovorum ( Pcc ) causes soft-rot disease in a wide variety of plants resulting in economic losses worldwide. It produces various types of bacteriocin to compete against related plant pathogens. Studies on how bacteriocins are extracellularly secreted are conducted to understand the mechanism of interbacterial competition. In this study, the secretion of the low-molecular-weight bacteriocins (LMWB) Carocin S1 and Carocin S3 produced by a multiple-bacteriocin producing strain of Pcc, 89-H-4, was investigated. Tn5 insertional mutagenesis was used to generate a mutant, TH22–6, incapable of LMWBs secretion. Sequence and homology analyses of the gene disrupted by transposon Tn5 insertion revealed that the gene sctT , an essential component of the injectisome type III secretion machinery (T3aSS), is required for the secretion of the bacteriocins. This result raised a question regarding the nature of the secretion mechanism of Pcc bacteriocins which was previously discovered to be secreted via T3bSS, a system that utilizes the bacterial flagellum for extracellular secretions. Our previous report has shown that bacteriocin Carocin S1 cannot be secreted by mutants that are defective of T3bSS-related genes such as flhA , flhC , flhD and fliC . We knocked out several genes making up the significant structural components of both T3aSS and T3bSS. The findings led us to hypothesize the potential roles of the T3aSS-related proteins, SctT, SctU and SctV, as flagellar T3SS chaperones in the secretion of Pcc bacteriocins. This current discovery and the findings of our previous study helped us to conceptualize a unique Type III secretion system for bacteriocin extracellular export which is a hybrid of the injectisome and flagellar secretion systems.